A bibliometric analysis of venture capital research - Christian A. Cancino; Jose Maria Merigo; Juan Pablo Torres-Martínez; David Díaz (Journal of Economics, Finance and Administrative Science, 2018)
The of this study is to present the evolution of academic research in venture capital (VC) research between 1990 and 2014. Design/methodology/approach The study analyzes the most influential journals in VC research by analyzing papers, which were published on the Web of Science database. Findings Results show a steady increasing rate of VC research during the past 25 years. The paper reports the 40 academic journals that permanently publish articles about VC research. Originality/value The main contribution of this work is to develop a general overview of the leading journals in VC research, which leads to the development of a future research agenda for bibliometric analysis, such as the review of the most productive and influential authors, universities and countries in VC research.
Keywords: 330; Web of science; Journals; Bibliometrics; Venture capital